Universal Design for Learning in K-12 Educational Settings: A Review of Group Comparison and Single-subject Intervention Studies - Crevecoeur, Yvel C; Sorenson, Sarah E; Mayorga, Victor; Gonzalez, Adriana P (Journal of Special Education Apprenticeship, 2014)
This literature review on Universal Design for Learning (UDL) included articles from January 1984 through June 2014. We (a) investigated the UDL educational framework without the inclusion of other major K-12 educational frameworks in learning environments, (b) reported researchers' scope and depth of use of the UDL principles, and (c) focused our investigation on two research methods: group comparison and single-subject. We used the quality indicators for evidence-based practices (EBPs) in special education to review, not rate, the final pool of five peer-reviewed articles. Results included analyses of the incorporation of UDL principles in all identified studies, highlighting the need for caution in promoting conceptual frameworks until sufficient empirical evidence is available to validate pedagogical utility in educational environments. We conclude that the UDL framework has merit but researchers must conduct studies that use group comparison and single-subject studies to independently test the UDL principles, guidelines, and checkpoints to increase the likelihood of causation in treatment outcomes.